Fitness and evolution of resprouters in relation to fire - Lamont, Byron; Enright, Neal; He, Tianhua (Springer Netherlands, 2011)
There are many ways that plants may recover vegetatively from dieback caused by fires. Compared with fire-killed species, the presence of woody resprouters in fire-prone floras increases with fire frequency, though this is affected by site productivity that may have opposing correlates along different gradients. Population recovery is enhanced by resprouting when fecundity is low and/or seedling recruitment is not guaranteed. There is resource cycling between vegetative growth and storage but no clear trade-off between fecundity and storage, and more attention needs to be given to the role of somatic mutations in reducing fecundity. Seven fitness benefits of post-fire resprouting are noted that centre around the rapid return to adult growth rates and early flowering and seed set without the risks of recruitment failure. The extent of resprouting at the individual, population, and species levels varies greatly but it is under genetic control. Recent studies on the evolution of resprouting in fire-prone systems have shown that types of resprouting (clonality, rootstocks, epicormic bud strands) are derived from surrounding parent lineages lacking these traits and confined to non-fire-prone environments. The oldest lineages with fire-related resprouting date to at least 61 million years ago, indicating that seed plants have had a long evolutionary relationship with fire. Various genetic mechanisms, including beneficial somatic mutations, have been invoked to explain how speciation of resprouters may keep pace with non-sprouters.